Solve the equation 8^(x-1) = 6^(3x) . Express your answer in terms of ln 2 and ln3 .

  • Google+ icon
  • LinkedIn icon
  • 4232 views

8(x-1) = 63x

23(x-1) = (2 * 3)3x

23x * 2-3 = 23x * 33x        / : 23x

2-3 = 33x                             / ln

ln(2-3) = ln(33x)

-3 ln(2) = 3x ln(3)         / :3

- ln(2) = x ln(3)

x = - ln(2)/ln(3)

David G. GCSE Maths tutor, IB Maths tutor

About the author

is an online IB Maths tutor with MyTutor studying at Edinburgh University

Still stuck? Get one-to-one help from a personally interviewed subject specialist.

95% of our customers rate us

Browse tutors

We use cookies to improve your site experience. By continuing to use this website, we'll assume that you're OK with this. Dismiss

mtw:mercury1:status:ok